Fintech Revolution: The Impact of Using Financial Technology on MSME Business Growth Through Financial Management Efficiency - Sukma, Paradisa; Priyambodo, Victoria Kusumaningtyas; Rizki, Novia; Devi, Ni Gusti Ayu Wiranti (Badan Penerbitan Fakultas Pertanian Universitas Ratu Samban, 2025)
Micro, Small, and Medium-Sized Enterprises (MSMEs) are vital to economic growth, but they often encounter a number of challenges, including poor financial management and restricted access to financing. This study aims to examine the influence of financial technology (fintech) adoption on MSME growth on Lombok Island, Indonesia, with financial management efficiency as a mediating variable. The study was conducted on 103 MSMEs and analyzed using the Partial Least Squares (PLS) method. The findings show that using fintech greatly increases MSME financial efficiency, and that increased financial efficiency has a favorable effect on company expansion. However, there was no correlation between the expansion of MSME and the use of fintech. These results demonstrate that the association between fintech adoption and MSME growth is significantly mediated by financial efficiency. Therefore, MSMEs must concentrate on using fintech to increase internal financial management efficiency if they want to reap the full benefits of this technology.